A state of secrecy Stasi informers and the culture of surveillance - Lewis, Alison, 1958- (Potomac Books, an imprint of the University of Nebraska Press, 2021)
A series of five interlaced, in-depth biographical studies from across the spectrum of writers-turned-spies recruited by the Stasi.